Acer truncatum Bunge seed oil attenuates learning and memory impairment in AD mouse model via modulating gut microbiota and metabolism - Ren, Duoduo; Chai, Xuejun; Xiang, Chenyao; Zhao, Yongkang; Sun, Penghao; Wang, Mengli; Li, Jing; Wu, Jiayue; Yi, Chenju; Chen, Shulin; Li, Enyao; Zhao, Shanting (Frontiers in Nutrition, 2026)
This study aimed to clarify the neuroprotective effect of Acer truncatum Bunge seed oil (ASO) and its interactions with the gut microbiota in transgenic mice with 5 × Familial Alzheimer's disease (5 × FAD). The AD-transgenic mice were fed with standard diet supplemented with 4% ASO from one to six months of age. The result show that ASO intervention can alleviate learning and memory impairment, enhance motor coordination and endurance, and reduce Aβ deposition in the brains. It also inhibit the proliferation of microglia and astrocytes, decrease the levels of IL-1β, IL-6, and TNF-α in the hippocampus and serum. Then, ASO could increase the Chao1 index and Shannon index, alter the gut microbiota composition, specifically, enhance the growth of gut bacteria correlated with the production of SCFAs, including Ruminococcaceae, Butyricicoccus, Sutterella and others, particularly those related to butyrate production. Additionally, ASO can increase the concentrations of SCFAs in fresh feces and serum, particularly butyric acid. ASO could primarily modulate the biosynthesis of unsaturated fatty acids, glycerophospholipid metabolism, and sphingolipids metabolism in serum. At the same time, Fecal microbiota transplantation (FMT) could reduce Aβ deposition, enhance learning and memory. Finally, Supplementation of sodium Buty also mitigate learning and memory impairments. This study highlights the gut microbiota might be a potential therapeutic target for AD and provides a scientific foundation for developing novel pharmaceuticals or nutraceuticals.